Enhanced enzymolysis and bioethanol yield from tobacco stem waste based on mild synergistic pretreatment - Gong, Jiang-Shi-Qi; Su, Jia-En; Cai, Jie-Yun; Zou, Ling; Chen, Yi; Jiang, Yong-Lei; Hu, Bin-Bin (Frontiers in Energy Research, 2023)
The use of mild pretreatment conditions can significantly lower the cost of the biorefining process. This study evaluated a mild pretreatment approach for tobacco stem waste using a combination of dilute acid and dilute alkali. By optimizing the pretreatment conditions, we obtained a high reducing sugar concentration at a pretreatment temperature <100°C. Increasing the acid or alkali strength in a single pretreatment step did not always improve the result; instead, the synergistic effect of both pretreatment components was important. To increase the bioethanol titer, a high solid loading, 30%, was used for bioethanol fermentation. Compared with batch fermentation, enzyme feeding with a shorter feeding period (24 h) enhanced the bioethanol production by 4.32%, generating 86.88 g/L bioethanol. The results provide valuable insights into the effects of two-step acid/alkali pretreatment on enzymolysis. The findings suggest that the optimized synergistic pretreatment process is efficient for bioethanol fermentation.